HUBUNGAN TINGKAT PENGETAHUAN MASYARAKAT DENGAN PERILAKU PENCEGAHAN COVID-19 DI DESA PAKUHAJI - Dellfi, Deane; Vebrian, Garry (Nusantara Hasana Berdikari, 2022)
COVID-19 is an infectious disease caused by a new type of coronavirus with general indications of fever, weakness, cough, convulsions and diarrhea. In Indonesia the incidence of COVID-19 as of March 31, 2021, patients continued to increase to 1.51 million cases with the addition of 5,937 (0.4%) confirmed cases, with 5,635 (0.37%) recovered patients, and died increased by 104 (0.007%). The PurposeÂ of the study to determine the relationship between the level of public knowledge and the behavior of preventing COVID-19 in Pakuhaji Village. Research methods using descriptive analytic with a cross sectional survey approach. Data collection using a questionnaire with a sample size of 223 samples. Sampling using random sampling and analysis test using chi-square. There is a relationship between the level of community knowledge and COVID-19 prevention behavior in Pakuhaji Village with p value = 0.000 â‰¤ 0.05. From the results of the study, there is a relationship between the level of public knowledge and COVID-19 prevention behavior.